Friends with Benefits: On Working with Ambiguity in Artistic Friendship-Collaborations - Angela Stiegler (The February Journal, 2025)
Friends with benefits was the title by which we—a group of three artist friends, Samuel Fischer-Glaser and Yulia Lokshina as well as this essay’s author—were invited to an exhibition in an artist-run space in Munich, Germany. The result was a 20-minute video installation that we framed as a music video for our imaginary vegan punk band by the same name: friends with benefits (2018/2023). We used this title as a name for our collaboration addressing the entanglements and sexual connotations that go along with it and expanded it to a diverse understanding of artistic collaboration. In this essay, we deal with what it means to be artists working in capitalist times and during multiple crises. We suggest a method for artistic collaborative work in Germany today. We embrace our working and living together, maneuvering continuously through problems and conflicts that emerge with the proximity of both work and life, friendship and love. Our common artistic strategies of collaboration include methods such as reading our own or others’ writings to each other, producing videos and re-using material already produced, a procedure we call ‘arte povera,’ and adding new layers of interpretation to it, thus exercising what in German is popularly known as ‘Verfremdungseffekt’ (literally: defamiliarizating effect). By reading and speaking in different registers, we gave the video material from 2018 a 2023 sound layer, in which we used our voices to perform different ideas of authorship and artisthood. By confronting ourselves with popular and problematic positions and by embodying them, we claim this as an ‘inconvenient’ method to develop critical thinking. Some of these voices that resound lead back to Munich as a site of avantgarde cultural production of New German Cinema as well as of two legendary and controversial figures of that movement, the director and actor Rainer Werner Fassbinder (1945–1982) and the actor Klaus Kinski (1926–1991). We also present ourselves as fictional musician characters that go on tour with their latest hit: Nie wieder Tier (‘Animal Never Again’). Through this setup, we ‘hope’ to approach ‘problematic’ situations in the present and address the symptoms of a still post-war German culture and the continuities of fascism.